Vitamin D deficiency and kidney hyperfiltration: a mechanism of kidney injury? - Fakhoury, Maya; Levy, Rebecca; Melamed, Michal L. (Annals of Translational Medicine, 2019)
Chronic kidney disease (CKD) is a public health problem, given that approximately 13% of adult Americans currently living with CKD (1). CKD is associated with a high risk of hospitalization, cardiovascular events and mortality (2).